Handbook of advanced ceramics : materials, applications, processing, and properties - Sōmiya, Shigeyuki (Academic Press, 2013)
This book includes sections on the basic science of advanced ceramics, functional ceramics (electro-ceramics and optoelectro-ceramics) and engineering ceramics.
Keywords: Ceramics.; elektronické knihy; electronic books